Christian realism and the new realities - Lovin, Robin W. (Cambridge University Press, 2008)
Are religion and public life really separate spheres of human activity? Should they be? In this book, Robin W. Lovin criticizes contemporary political and theological views that separate religion from public life as though these areas were systematically opposed and makes the case for a more integrated understanding of modern society. Such an understanding can be underpinned by 'Christian realism', which encourages responsible engagement with social and political problems from a distinctive perspective. Drawing on the work of Rawls, Galston, Niebuhr, and Bonhoeffer, Lovin argues that the responsibilities of everyday life are a form of politics. Political commitment is no longer confined to the sphere of law and government, and a global ethics arises from the decisions of individuals. This book will foster a better understanding of contemporary political thought among theologians and will introduce readers primarily interested in political thought to relevant developments in recent theology.